Flora and syntaxonomy of communities including Juniperus oblonga M. Bieb. on the Gunib Plateau - G. A. Sadykova (Юг России: экология, развитие, 2022)
Aim. To identify and describe communities which include Juniperus oblonga on the Gunib Plateau. To conduct a taxonomic, geographical, biomorphological analysis of the flora of these communities.Material and Methods. The research was carried out by the method of the laying of trial plots. 15 geobotanical descriptions were undertaken. Office data processing was carried out using tabular ecological‐phytocenotic analysis. Analysis of the flora of the communities was carried out according to generally accepted methods of floristic research.Results. The flora of the juniper woodlands of the Gunib Plateau is represented by 185 species from 124 genera and 41 families. According to the results of geographical analysis, 19 geoelements were identified from 4 geotypes, of which the species of the boreal group (53.8%) of the Caucasian geoelement (31.9%) are the most represented. There are present rare and disappearing (2.7%), endemic (28.1%) and relict species (14.1%). An ecological‐phytocenotic classification of communities with the participation of Juniperus oblonga on the Gunib Plateau was developed and 4 associations, 5 subassociations and 5 variants were identified. A prodromus was compiled.Conclusion. Sparse juniper forests are one of the main types of vegetation of the Gunib Plateau, constituting a third of the flora of the plateau with a high degree of uniqueness and a complex of abiotic factors that change along the altitudinal gradient, microrelief and slope exposures, which are decisive when dominants change in communities of sparse juniper forests.